2013
DOI: 10.1074/jbc.m113.465369
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Degradation of the Arabidopsis Transcription Factor ABSCISIC ACID INSENSITIVE 5 Is Mediated by the RING-type E3 Ligase KEEP ON GOING

Abstract: Background: KEEP ON GOING (KEG) is required to maintain low levels of the nuclear-localized transcription factor ABI5. Results: KEG-mediated degradation of ABI5 occurs in the cytoplasm/trans-Golgi network/early endosome and requires a C-terminal lysine residue. Conclusion: Cytoplasmic degradation prevents nuclear accumulation of ABI5 so as to prohibit ABA signaling. Significance: Knowing how ABI5 stability is controlled is crucial to understanding ABA signaling and plant survival of environmental stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
105
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(112 citation statements)
references
References 33 publications
7
105
0
Order By: Relevance
“…A. tumefaciens strain GV3101 transformed with the appropriate binary plasmids was grown and prepared for transient expression as described previously (Sparkes et al, 2006;Liu and Stone, 2013). Briefly, A. tumefaciens cultures were resuspended in infiltration solution (5 mg mL 21 D-Glc, 50 mM MES, 2 mM Na 3 PO 4 , and 0.1 mM acetosyringone) at an optical density at 600 nm of 0.8.…”
Section: Transient Protein Expression In Tobaccomentioning
confidence: 99%
“…A. tumefaciens strain GV3101 transformed with the appropriate binary plasmids was grown and prepared for transient expression as described previously (Sparkes et al, 2006;Liu and Stone, 2013). Briefly, A. tumefaciens cultures were resuspended in infiltration solution (5 mg mL 21 D-Glc, 50 mM MES, 2 mM Na 3 PO 4 , and 0.1 mM acetosyringone) at an optical density at 600 nm of 0.8.…”
Section: Transient Protein Expression In Tobaccomentioning
confidence: 99%
“…The Arabidopsis genome is predicted to contain more than 460 RING-containing proteins (Stone et al, 2005). Although the function of several RING proteins has been studied extensively (Dong et al, 2006;Stone et al, 2006;Lau and Deng, 2012;Lazaro et al, 2012Lazaro et al, , 2015Liu and Stone, 2013;Lee and Seo, 2015;Pauwels et al, 2015;Wang et al, 2015a), the E3 ligase activity and the targets of most RING proteins in Arabidopsis have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…KEG is a RING-finger E3 ligase that has been previously shown to regulate abscisic acid signaling through mediating degradation of the transcription factors ABSCISIC ACID INSENSITIVE5 (ABI5), ABA BINDING FACTOR1 (ABF1), and ABF3 (Stone et al, 2006;Liu and Stone, 2010;Chen et al, 2013). We have previously shown that KEG physically associates with the kinase domain of EDR1 on trans-Golgi network/early endosome (TGN/EE) vesicles , while Liu and Stone (2013) have recently shown that KEG physically associates with ABI5 on TGN/EE vesicles. Together, these data suggest that EDR1 may function at the TGN/EE and regulate the E3 ligase activity of KEG.…”
Section: Introductionmentioning
confidence: 99%